Characterization of 5.5 GHz High Gain Microstrip 2x2 Array Antenna - Irfan Mujahidin (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
This paper presents the plan of the microstrip cluster radio wire on the 5.5GHz C Band application. The proposed radio wire comprises 4 rectangular patches with a microstrip line nourishing arrange set up employing a transformer impedance quarter wavelength coordinating strategy. On dodge grinding flaps influenced by the between patches dispersing, the fixed division to the adjoining radiation element is the collection to be wavelength with the value is 0.5. Thus, to realize tall pick up required by the 5.5GHz C Band details, the cluster comprised of 4 radiation element is connected where the radiation element is organized in 2x2 (pile x lines) arrangement. The receiving wire configuration is at that point conveyed on a phonetic white paper substrate in what the misfortune, digression thickness, and dielectric steady are 0.0016cm, 4.2, and 0.0001, separately. The Identification result of return loss, radiation design, pick up, and impedance coordinating are displayed continuously. From the result, it appears that the proposed receiving wire has a generally pick up of 8.95dB and the return mismatch of 32.98dB.